Формування сучасного навчального інформаційного середовища на морфологічних кафедрах у медичному ВНЗ - Сирцов, Вадим Кирилович; Алієва, Олена Геннадіївна; Полковніков, Юрій Федорович; Зідрашко, Галина Анатоліївна; Потоцька, Олена Іванівна; Сырцов, В. К.; Алиева, Е. Г.; Полковников, Ю. Ф.; Зидрашко, Г. А.; Потоцкая, Е. И.; Sirtsov, V. K.; Aliyeva, O. G.; et al. (My University, 2016)
Стратегія перебудови вищої медичної освіти України в зв’язку з процесом її інтеграції в європейський освітній простір передбачає використання нових ефективних інформаційних технологій, оновлення змісту освіти, формування навчального інформаційного середовища. Морфологічні кафедри ЗДМУ активно беруть участь у створенні інформаційно-освітнього середовища університету. Процес створення єдиного інформаційного середовища ВНЗу за допомогою нових сучасних технологій носить багатогранний і комплексний характер. Інформатизація освіти створює нове середовище, що дозволяє оптимально поєднувати звичайні і комп’ютерні форми організації навчального процесу, дає нову якість в передачі і засвоєнні системи знань, засвоєнні практичних навичок майбутніх лікарів. Стратегия перестройки высшего медицинского образования Украины в связи с процессом ее интеграции в европейское образовательное пространство предполагает использование новых эффективных информационных технологий, обновление содержания образования, формирования учебной информационной среды. Морфологические кафедры ЗГМУ активно участвуют в создании информационно-образовательной среды университета. Процесс создания единой информационной среды вуза с помощью новых современных технологий носит многогранный и комплексный характер. Информатизация образования создает новую среду, что позволяет оптимально сочетать обычные и компьютерные формы организации учебного процесса, дает новое качество в передаче и усвоении системы знаний, усвоении практических навыков будущих врачей. The strategy of reforming of medical higher education in Ukraine in connection with the process of its integration into the European educational field provides for the use of new effective information technologies, education contents renewing, forming of educational information environment. The experience of morphology chairs of Zaporizhzhia medical university in forming of educational information environment and introducing of information technologies into the process of teaching and studying has been analyzed in this thesis. The main components of educational information environment (these are content, technologies and organization), that were the target of the monitoring, have been defined in the process of analyzing. The educational information environment includes the system of information and educational resources on different carriers, the system of pedagogical technologies and personnel and the combination of training aids that provide both the effective cooperation between the participants of the educational process and institutional and economical mechanisms. The introduction of information technologies into all the components of the educational process is the key basis of forming of the educational information field. Information technologies are the educational technologies that use special means, software and hardware (personal computers, audio, video, films) for the information work. The use of new information technologies, especially those of communication kind, enables the increase of studying motivation, individualization and differentiation of studying process and basing on the individually oriented studying. The morphology chairs of ZSMU take active part in creating university information and education environment. Introduction of information technologies into the studying process at the morphology chairs is defined by the following factors: equipping chairs with up-to-date personal computers, educational software and information, lecturers’ qualification level in the field of information technologies, students’ computer skills. The use of information technologies at the morphology chairs includes next forms: multimedia materials for lectures, training and assessment computer testing, educational programs and animation, videos, electronic textbooks, manuals and workbooks, 3D models of anatomical and histological structures, placing educational material in all the subjects at chairs web pages of the university web site, taking part in forming electronic library information complex, electronic register. The process of creating of common information environment of a higher school with the help of new up-to-date technologies is many-sided and complex and requires lecturers’ advanced level of subject expertise and computer skills. Informatization of education creates new environment. It enables, basing on students’ individual needs, the development of such an education scheme in which optimal combination of regular and computer forms of education process organization provides new quality of knowledge system transmitting and learning and mastering of future doctors’ practical skills.
Формирование современной учебной информационной среды на морфологических кафедрах в медицинском вузе
Forming of modern educational information environment at morphology chairs of a medical higher school
Keywords: навчальне інформаційне середовище; інформаційні комп’ютерні технології; вища медична освіта; навчальний процес; учебная информационная среда; информационные компьютерные технологии; высшее медицинское образование; учебный процесс; educational information environment; information computer technologies; medical higher education; education process